The effect of emigration on the Hungarian labour market - Katalin Bodnár; Lajos Tamás Szabó (Magyar Nemzeti Bank, 2014)
In our analysis, we examine the effects of emigration from Hungary on the labour market and its other economic implications. Since 2008 the number of emigrants has been rising significantly faster than the previous trend, and thus it is important to assess the possible consequences of higher mobility in the Hungarian economy. We focus primarily on the effects on wages, for which it is indispensable to give an overview of the productivity effects as well. To that end, we need to gain a deeper insight into the characteristics of emigrants. As the information in the database available to us is limited to a single segment of those working abroad, namely cross-border commuters, this is the only group for which we can provide a detailed description. We find that the number of cross-border commuters is growing especially rapidly among skilled workers with secondary qualifications and among those employed in the sectors of construction, accommodation and food service activities. As regards age groups, younger generations account for a dominant portion of commuters. Based on the individual characteristics of commuters we assume that cyclical reasons may have contributed significantly to the rise in emigration. At this time, it is difficult to gauge the full impact of emigration on wages, productivity, growth and sustainability, as these factors depend partly on future growth rate of emigration and on the extent to which those working abroad return to the Hungarian labour market.
Keywords: E24; E6; F22; 330; emigration; labour force survey; labour market